Succinate as a Regulator of Hepatic Stellate Cells in Liver Fibrosis - Cho, Eun-Hee (Frontiers in Endocrinology, 2018)
The rapid increase of obesity rates worldwide is associated with chronic liver injury due to non-alcoholic fatty liver disease and non-alcoholic steatohepatitis. Chronic liver inflammation drives hepatic fibrosis, which is a highly conserved and coordinated protective response to tissue injury, and is a reversible process. Hepatocytes, immune cells, and hepatic stellate cells (HSCs) have been identified as key players in the mechanisms of hepatic fibrosis and inflammation. During the last decade, succinate, an intermediate of the tricarboxylic acid cycle in mitochondrial ATP production, has emerged as an important signaling molecule in various diseases. Succinate acts as an extracellular ligand for G-protein coupled receptor 91, also known as succinate receptor 1, which is mainly expressed in the kidney, heart, liver, immune cells, and retinal cells, suggesting a widespread function in cellular metabolism. Furthermore, succinate stabilizes hypoxia-inducible factor-1α in immune cells and tumors as a signaling molecule, and has been shown to post-translationally modify proteins. This review summarizes the recent evidence pointing to an additional role of succinate in profibrotic signaling, along with its downstream signaling pathways, and updates the current state of knowledge on the role of succinate in liver fibrosis through its action on HSCs. Further focus on this link can help identify succinate, its receptor, and its downstream signaling molecules as new targets for the treatment of liver fibrosis.